Explosive Parameters for Coal Samples (Antioquia, Colombia) (2018)
Through proximate analysis (residual moisture, RM, ashes, As, volatile matter, VM, fixed carbon, FC, total Sulphur, TS and calorific value, CV), granulometric, minimum cloud ignition temperature tests (TMIn), lower explosion limit (LEL) and explosion severity (Kmáx); it is proposed to identify which coal produces the most explosive dust. For most samples, the highest amount of coal particle volume is between 100 μm and 200 μm. For the Amagá sample, the volume of particles smaller than 10 μm is the largest, which agrees with the results of the TMIn, which is the lowest (400 °C), the lowest LEL (30 g/m3) and the highest Kmáx value (176 bar, m/s). On the contrary, the Angelópolis sample presents a very skewed curve towards sizes between 60 μm and 300 μm, therefore, its TMIn is the highest (480 °C) of the Eastern Zone of the Sinifaná basin and its LEL is under 60 g/m3, and it also presents the lowest value of Kmáx (106 bar, m/s), thus, it is observed that there is a direct relationship between the granulometry and the results of severity and sensitivity to the explosion. In general, there is a different behavior between the samples of the municipalities of Amagá and Titiribí, especially between the LIE and the results of the analyses of VM, FC and CV, with respect to the other samples, which is also in agreement with their greater susceptibility to inflammation and explosiveness.